Flexible conductive film and preparation method thereof, and flexible pressure sensor
By using a flexible conductive film with a multi-level pyramid microstructure in a flexible pressure sensor, the problem of difficulty in taking into account the sensitivity and detection range in traditional microstructure design is solved, and a flexible pressure sensor with high sensitivity and wide detection range is realized.
Patent Information
- Application Number
- CN202310747223.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
AI Technical Summary
Flexible pressure sensors prepared by traditional microstructure designs are difficult to maintain high sensitivity while having a wide detection range.
Using a flexible conductive film with a multi-layered pyramid microstructure, multi-layered processing processes such as self-assembly, reactive ion etching, magnetron sputtering deposition and wet etching on a hydrophilic silicon substrate, multi-layered processing technology is formed. Pyramid microstructure, increasing the number of levels to increase the degree of deformation.
The sensitivity and detection range of flexible pressure sensors are improved, while the reliability is enhanced, significantly expanding the number of levels and deformation degree of multi-level pyramid microstructures.
Smart Images

Figure CN119181527A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sensor technology, and in particular to a flexible conductive film and a preparation method thereof, and a flexible pressure sensor. Background Art
[0002] In recent years, wearable flexible pressure sensors have broad application prospects in human health monitoring, disease pre-diagnosis, motion monitoring, human-computer interaction, etc. due to their light, thin, and flexible characteristics and their ability to sensitively respond to the pressure generated by human activities. Microstructure design is an effective way to improve the performance of flexible pressure sensors. However, it is still difficult for flexible pressure sensors prepared using traditional microstructure design to maintain high sensitivity while also having a wide detection range. Summary of the invention
[0003] Based on this, it is necessary to provide a flexible conductive film and a preparation method thereof, and a flexible pressure sensor to address the problem that flexible pressure sensors prepared using traditional microstructure designs still find it difficult to maintain high sensitivity while having a wide detection range. The flexible conductive film prepared by the preparation method has excellent performance, and the flexible pressure sensor prepared based on the flexible conductive film can improve the sensitivity while also improving the detection range and reliability.
[0004] The present invention provides a method for preparing a flexible conductive film, comprising the following steps:
[0005] Provide hydrophilic and crystalline <100> A silicon substrate, a flexible conductive mixed liquid, a mixed liquid containing at least two first colloidal microspheres of different diameters, and a mixed liquid containing second colloidal microspheres of a single diameter;
[0006] A mixed solution containing at least two first colloidal microspheres of different diameters is placed in a hydrophilic and crystallographically oriented <100> The silicon substrate is self-assembled to form a single-layer first colloidal microsphere film, wherein the diameter of the first colloidal microsphere is 1 μm-500 μm, and the diameter ratio of any two first colloidal microspheres with different diameters is A, 1:1<A≤4:1;
[0007] Performing reactive ion etching on the first colloidal microsphere film, and then performing magnetron sputtering deposition to form a first metal layer, removing the first colloidal microspheres, and then performing wet etching to obtain a first pyramid microstructure silicon template;
[0008] The first pyramid microstructure silicon template is subjected to hydrophilic treatment, and then the mixed solution containing second colloidal microspheres of a single diameter is self-assembled on the surface of the first pyramid microstructure silicon template to form a single-layer second colloidal microsphere film, wherein the diameter of the second colloidal microspheres is 5%-20% of the diameter of the first colloidal microspheres;
[0009] Performing reactive ion etching on the second colloidal microsphere film, and then performing magnetron sputtering to form a second metal layer, removing the second colloidal microspheres, and then performing wet etching to obtain a multi-level pyramid microstructure silicon template; and
[0010] The flexible conductive mixed liquid is placed on the surface of the multi-level pyramid microstructure silicon template, and after curing and peeling, a flexible conductive film with a multi-level pyramid microstructure on the surface is obtained.
[0011] In one embodiment, the mixed solution containing at least two first colloidal microspheres of different diameters is obtained by mixing at least two stock solutions of first colloidal microspheres of different diameters and anhydrous ethanol, wherein the volume ratio of the stock solutions of any two first colloidal microspheres of different diameters is M, 1:1≤M≤8:1, and M represents the volume ratio of the stock solution of the first colloidal microspheres with a larger diameter to the stock solution of the first colloidal microspheres with a smaller diameter.
[0012] In one embodiment, before placing the flexible conductive mixed liquid on the surface of the multi-level pyramid microstructure silicon template, the surface of the multi-level pyramid microstructure silicon template is subjected to a hydrophobic treatment.
[0013] In one embodiment, the self-assembly is performed by air-liquid-interface self-assembly;
[0014] And / or, the first colloidal microspheres and the second colloidal microspheres are both selected from at least one of polystyrene colloidal microspheres, polymethyl acrylate colloidal microspheres, polyacrylamide colloidal microspheres, and polybutyl acrylate colloidal microspheres.
[0015] In one embodiment, during the reactive ion etching process, oxygen is used as the etching gas, the etching power is 50W-100W, and the etching time is 2min-120min;
[0016] and / or, during the wet etching process, the etching temperature is 80° C.-90° C., and the etching time is 2 min-60 min;
[0017] And / or, during the curing process, the curing temperature is 25° C.-150° C., and the curing time is 0.25 h-24 h.
[0018] In one embodiment, the thickness of the first metal layer and the second metal layer are both 50nm-100nm.
[0019] In one embodiment, the flexible conductive mixed liquid is formed by mixing polymer monomers, conductive materials and curing agents, wherein the mass fraction of the conductive materials in the flexible conductive mixed liquid is 5%-15%.
[0020] In one embodiment, the material of the polymer monomer is selected from at least one of polydimethylsiloxane, polyurethane elastomer, and polytrimethylene carbonate;
[0021] And / or, the conductive material is selected from at least one of carbon nanotubes, graphene, and silver nanowires.
[0022] The present invention also provides a flexible conductive film, which is prepared by the above-mentioned method for preparing a flexible conductive film. The surface of the flexible conductive film has a multi-level pyramid microstructure, and the multi-level pyramid microstructure includes a first pyramid and a second pyramid arranged on the side wall of the first pyramid, wherein the height of the first pyramid is 500nm-200μm, and the height of the second pyramid is 100nm-100μm.
[0023] A flexible pressure sensor, comprising:
[0024] A first substrate, wherein the first substrate is the flexible conductive film as described above;
[0025] The second substrate includes a flexible substrate and an electrode disposed on a surface of the flexible substrate. The second substrate is stacked on the first substrate, and the electrode contacts a portion of the multi-level pyramid microstructure to obtain a flexible pressure sensor.
[0026] In the method for preparing the flexible conductive film of the present invention, in the process of preparing the multi-level pyramid microstructure silicon template, a mixed solution containing at least two first colloidal microspheres with different diameters is firstly used to prepare a first colloidal microsphere having hydrophilicity and a crystal orientation of <100> Self-assembly, reactive ion etching, magnetron sputtering deposition, wet etching and other micro-nano processing techniques are performed on a silicon substrate, so that the formed first pyramid microstructure has two or more different height sizes, that is, at least two levels of pyramid microstructures are formed, and then self-assembly, reactive ion etching, magnetron sputtering deposition, wet etching and other micro-nano processing techniques are performed with a mixed liquid containing second colloidal microspheres of a single diameter to form a second pyramid microstructure on the side wall of the first pyramid microstructure, so that the first pyramid microstructure itself increases at least one more level, thereby greatly increasing the number of levels of the multi-level pyramid microstructure, and as the number of levels increases, the deformability of the multi-level pyramid microstructure also increases.
[0027] At the same time, by controlling the diameter ratio of at least two first colloidal microspheres of different diameters to A, 1:1<A≤4:1, the height difference between first pyramid microstructures of different sizes is regulated, and further by controlling the diameter of the second colloidal microsphere to 5%-20% of the diameter of the first colloidal microsphere, a multi-level effective second pyramid microstructure is formed on the side wall of the first pyramid microstructure, thereby increasing the number of levels of each first pyramid microstructure, thereby obtaining a multi-level pyramid microstructure with an extremely high number of levels, significantly increasing the deformability of the multi-level pyramid microstructure, and thereby enabling the prepared flexible pressure sensor to improve sensitivity while also improving detection range and reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a process flow chart of preparing a flexible conductive film according to one embodiment of the present invention;
[0029] Figure 2 It is a schematic structural diagram of a flexible pressure sensor according to one embodiment of the present invention;
[0030] Figure 3 The figure is a curve diagram showing the relationship between the current change rate and the pressure of the flexible pressure sensors prepared in Example 2 of the present invention and Comparative Examples 1-6.
[0031] In the figure: 1. first substrate; 2. multi-level pyramid microstructure; 3. second substrate; 4. first pyramid; 5. second pyramid. DETAILED DESCRIPTION
[0032] The flexible conductive film and its preparation method, and the flexible pressure sensor provided by the present invention will be further described below.
[0033] like Figure 1 As shown, the method for preparing the flexible conductive film provided by the present invention comprises the following steps:
[0034] S1, provide hydrophilic and crystal orientation <100> A silicon substrate, a flexible conductive mixed liquid, a mixed liquid containing at least two first colloidal microspheres of different diameters, and a mixed liquid containing second colloidal microspheres of a single diameter;
[0035] S2, placing a mixed solution containing at least two first colloidal microspheres of different diameters in a hydrophilic <100> The silicon substrate is self-assembled to form a single-layer first colloidal microsphere film, wherein the diameter of the first colloidal microsphere is 1 μm-500 μm, and the diameter ratio of any two first colloidal microspheres with different diameters is A, 1:1<A≤4:1;
[0036] S3, performing reactive ion etching on the first colloidal microsphere film, and then performing magnetron sputtering deposition to form a first metal layer, removing the first colloidal microspheres, and then performing wet etching to obtain a first pyramid microstructure silicon template;
[0037] S4, subjecting the first pyramid microstructure silicon template to hydrophilic treatment, and then self-assembling a mixed solution containing second colloidal microspheres of a single diameter on the surface of the first pyramid microstructure silicon template to form a single-layer second colloidal microsphere film, wherein the diameter of the second colloidal microspheres is 5%-20% of the diameter of the first colloidal microspheres;
[0038] S5, performing reactive ion etching on the second colloidal microsphere film, and then performing magnetron sputtering to form a second metal layer, removing the second colloidal microspheres, and then performing wet etching to obtain a multi-level pyramid microstructure silicon template; and
[0039] S6, placing the flexible conductive mixed liquid on the surface of the multi-level pyramid microstructure silicon template, and obtaining a flexible conductive film with a multi-level pyramid microstructure on the surface through curing and peeling.
[0040] In the method for preparing the flexible conductive film of the present invention, in the process of preparing the multi-level pyramid microstructure silicon template, a mixed solution containing at least two first colloidal microspheres with different diameters is firstly used to prepare a first colloidal microsphere having hydrophilicity and a crystal orientation of <100> Self-assembly, reactive ion etching, magnetron sputtering deposition, wet etching and other micro-nano processing techniques are performed on a silicon substrate, so that the formed first pyramid microstructure has two or more different height sizes, that is, at least two levels of pyramid microstructures are formed, and then self-assembly, reactive ion etching, magnetron sputtering deposition, wet etching and other micro-nano processing techniques are performed with a mixed liquid containing second colloidal microspheres of a single diameter to form a second pyramid microstructure on the side wall of the first pyramid microstructure, so that each first pyramid microstructure itself increases at least one more level, thereby greatly increasing the number of levels of the multi-level pyramid microstructure, and as the number of levels increases, the deformability of the multi-level pyramid microstructure also increases.
[0041] At the same time, by controlling the diameter ratio of at least two first colloidal microspheres of different diameters to A, 1:1<A≤4:1, the height difference between first pyramid microstructures of different sizes is regulated, and further by controlling the diameter of the second colloidal microsphere to 5%-20% of the diameter of the first colloidal microsphere, a multi-level effective second pyramid microstructure is formed on the side wall of the first pyramid microstructure, thereby increasing the number of levels of each first pyramid microstructure, thereby obtaining a multi-level pyramid microstructure with an extremely high number of levels, significantly increasing the deformability of the multi-level pyramid microstructure, and thereby enabling the prepared flexible pressure sensor to improve sensitivity while also improving detection range and reliability.
[0042] In step S1, the hydrophilic <100> The method for preparing a silicon substrate with a crystal orientation of <100> The silicon wafer is placed in a mixed solution of ammonia water, hydrogen peroxide and deionized water, and heated to 140°C-160°C for hydrophilic treatment for 8min-12min, wherein the volume ratio of the ammonia water, the hydrogen peroxide and the deionized water is 1:(1-3):(4-8), and then repeatedly washed with clean water and dried to obtain a hydrophilic silicon wafer with a crystal orientation of <100> Preferably, the volume ratio of the ammonia water, the hydrogen peroxide solution and the deionized water is 1:2:6, which is convenient for subsequent self-assembly of the mixed solution containing the first colloidal microspheres.
[0043] In step S1, the flexible conductive mixed liquid is mixed by polymer monomers, conductive materials and curing agents, wherein the mass fraction of the conductive material is 5%-15%, and the mass ratio of the polymer monomers to the curing agent is 10:(0.9-1.1). Preferably, the mass ratio of the polymer monomers to the curing agent is 10:1. Such a setting can make the prepared flexible conductive mixed liquid have better fluidity, so that it can be better placed in the multi-level pyramid microstructure silicon template, thereby obtaining a flexible conductive film with a multi-level pyramid microstructure on the surface, and at the same time make the flexible conductive film have excellent conductivity, thermal stability and flexibility.
[0044] In one embodiment, the material of the polymer monomer is selected from at least one of polydimethylsiloxane, polyurethane elastomer, and polytrimethylene carbonate. Since polydimethylsiloxane has the best biocompatibility and thermal stability, polydimethylsiloxane is preferably used in the present invention. This arrangement further improves the flexibility of the flexible conductive film.
[0045] Furthermore, the conductive material is selected from at least one of carbon nanotubes, graphene, and silver nanowires. The present invention preferably uses carbon nanotubes, so that the flexible conductive film can have better flexibility while improving the conductivity of the flexible conductive film.
[0046] In one embodiment, the preparation method of the flexible conductive mixed liquid is as follows: disperse the conductive material in an organic solvent, ultrasonically stir for 5 minutes to 30 minutes, and then magnetically stir or mechanically stir for 0.5 hours to 1 hour, wherein the organic solvent is selected from tetrahydrofuran, n-hexane, cyclohexane, preferably tetrahydrofuran, and then add the polymer monomer, continue to stir evenly, and heat in a water bath at 60°C to 70°C to volatilize the organic solvent, then add the curing agent, stir evenly at room temperature, and finally place under vacuum conditions for 30 minutes to 60 minutes to remove bubbles to obtain a flexible conductive mixed liquid.
[0047] In one embodiment, in step S1, a mixed solution containing at least two first colloidal microspheres with different diameters is obtained, and the specific process is as follows: at least two stock solutions of first colloidal microspheres with different diameters are mixed to obtain a mixed stock solution, and then an anhydrous ethanol solution is added, ultrasonically treated for 5min-20min, and mixed evenly to obtain a mixed solution containing first colloidal microspheres, wherein the volume ratio of the mixed stock solution to anhydrous ethanol is 1:1.1-1:1.3, preferably 1:1.2.
[0048] In step S1, a mixed solution containing second colloidal microspheres of a single diameter is obtained, and the specific process is as follows: the stock solution of the second colloidal microspheres of a single diameter is mixed with anhydrous ethanol to obtain a mixed solution containing the second colloidal microspheres, wherein the volume ratio of the stock solution of the second colloidal microspheres of a single diameter to anhydrous ethanol is 1:1.1-1:1.3, preferably 1:1.2.
[0049] In step S2, the diameter of the first colloidal microspheres is 1 μm-500 μm, and the diameter ratio of any two first colloidal microspheres with different diameters is A, 1:1<A≤4:1, preferably, the diameter ratio of any two first colloidal microspheres with different diameters is 2:1. In this way, the mixed solution containing the first colloidal microspheres is placed in a hydrophilic and crystallographically oriented <100> When the silicon substrate surface is formed, the first colloidal microspheres of two or more different diameters can be evenly distributed on the hydrophilic and crystal-oriented surface through the capillary force and electrostatic repulsion between the first colloidal microspheres. <100> on the surface of the silicon substrate and form a monolayer of the first colloidal microsphere film, that is, a close-packed array of first colloidal microspheres of at least two different diameters is obtained, thereby preparing a multi-level pyramid microstructure silicon template.
[0050] In order to better prepare the multi-level pyramid microstructure, preferably, in the mixed solution containing at least two first colloidal microspheres of different diameters, the original solution volume ratio of any two first colloidal microspheres of different diameters is M, which is 1:1≤M≤8:1, and M represents the volume ratio of the original solution of the first colloidal microspheres with larger diameters to the original solution of the first colloidal microspheres with smaller diameters. Such a setting facilitates the number of more than two first colloidal microspheres of different diameters to be in a balanced state, so as to prevent the local aggregation of the first colloidal microspheres of a certain diameter from being excessive, affecting the distribution uniformity of the first colloidal microspheres of more than two different diameters on the surface of the silicon substrate, thereby affecting the distribution uniformity of the multi-level pyramid microstructure, and further affecting the performance stability of the prepared flexible pressure sensor.
[0051] In step S2, the diameter of the second colloidal microspheres is 5%-20% of the diameter of the first colloidal microspheres. This arrangement makes it easier for the second colloidal microspheres to be evenly distributed on the surface of the first pyramid microstructure silicon template through the capillary force and electrostatic repulsion between the second colloidal microspheres in the subsequent step S4 to form a single-layer second colloidal microsphere film, and it is also easier to form second pyramid etch pits on the side walls of the first pyramid etch pits in the first pyramid microstructure silicon template, thereby forming a multi-level pyramid microstructure silicon template.
[0052] In one embodiment, in step S2 or step S4, the self-assembly is performed by gas-liquid interface self-assembly. For example, in step S2, specifically: using a pipette, the mixed solution containing the first colloidal microspheres is transferred from a hydrophilic and crystal-oriented liquid at an angle of 30°-60° to a liquid containing the first colloidal microspheres. <100> The higher side of the silicon substrate is along the hydrophilic and crystal orientation <100> The mixed solution containing the first colloidal microspheres is extruded along the hydrophilic and crystal-oriented <100> The silicon substrate is flowed down and has hydrophilicity and a crystal orientation of <100> The silicon substrate surface is naturally diffused, and then the hydrophilic and crystal orientation <100> The silicon substrate is tilted 15°-45° and slowly and evenly placed into a container filled with plasma water to make it hydrophilic and with a crystal orientation of <100> The first colloidal microspheres on the surface of the silicon substrate float and spread on the water-air interface, then 1-3 drops of 10% SDS (sodium dodecyl sulfate) solution are dripped into the water at the edge of the container to aggregate the first colloidal microspheres on the water surface to form a single-layer first colloidal microsphere film, and then tweezers are used to clamp a clean hydrophilic and crystal-oriented <100> The first colloidal microsphere film is lifted from the water surface at an angle of 40°-50°, or the hydrophilic and crystal-oriented <100> The silicon substrate is placed at the bottom of the water container, and the water is drained using a peristaltic pump so that the first colloidal microsphere film on the water surface naturally falls to the hydrophilic and crystal-oriented <100> on a silicon substrate.
[0053] In one embodiment, the first colloidal microspheres and the second colloidal microspheres are both selected from at least one of polystyrene colloidal microspheres, polymethyl acrylate colloidal microspheres, polyacrylamide colloidal microspheres, and polybutyl acrylate colloidal microspheres.
[0054] In step S3, the first colloidal microsphere film is subjected to reactive ion etching, wherein oxygen is used as etching gas, the etching power is 50W-100W, and the etching time is 2min-120min. This arrangement facilitates the first colloidal microspheres densely packed on the surface of the silicon substrate to be etched small and separated from each other.
[0055] Afterwards, magnetron sputtering deposition is performed to form a first metal layer, wherein the thickness of the first metal layer is 50nm-100nm, and the first metal layer can be a gold layer or a chromium layer. Then, the first colloidal microspheres are removed using tape or an organic solvent, wherein the organic solvent is selected from at least one of acetone, chloroform, xylene, and toluene, thereby forming uniformly distributed metal holes of different diameters on the silicon substrate, so that it can serve as a mask in subsequent processes.
[0056] Next, wet etching is performed, specifically, anisotropic etching of the silicon substrate is performed using an alkaline solution. Due to the different diameters of the metal holes on the silicon substrate, that is, the different areas of the silicon substrate exposed to the etching solution, the width and depth of the etching pits (inverted pyramid shape) on the silicon substrate are different, forming first pyramid etching pits of different sizes, and obtaining a first pyramid microstructure silicon template. The alkaline solution is selected from NaOH solution or KOH solution, the etching temperature is 80°C-90°C, and the etching time is 2min-60min.
[0057] In one embodiment, Aladdin (S128515) sodium hydroxide standard solution is used for wet etching.
[0058] In one embodiment, in step S5, reactive ion etching is performed on the second colloidal microsphere film to etch the second colloidal microspheres into small pieces so as to be separated from each other, and then magnetron sputtering is performed to form a second metal layer, wherein the thickness of the second metal layer is 50nm-100nm, and the second metal layer is a gold layer or a chromium layer, and then an organic solvent is used to remove the second colloidal microspheres, wherein the organic solvent is selected from at least one of acetone, chloroform, xylene, and toluene, thereby forming metal holes of a single diameter on the surface of the first pyramid microstructure silicon template, so that it can serve as a mask in subsequent processes.
[0059] Next, wet etching is performed, and the first pyramid microstructure silicon template is anisotropically etched using an alkaline solution, so as to continue to etch a second pyramid etch pit on the first pyramid microstructure silicon template. Since the diameter of the second colloidal microsphere is 5%-20% of the diameter of the first colloidal microsphere, the formed second pyramid etch pit is located on the side wall of the first pyramid etch pit, thereby obtaining a multi-level pyramid microstructure silicon template.
[0060] It should be noted that in the reactive ion etching process of the present invention, the etching power and etching time are determined by the diameter of the first colloidal microspheres or the second colloidal microspheres. The larger the diameter of the first colloidal microspheres or the second colloidal microspheres, the smaller the etching power or etching time can be adjusted, as long as the microspheres are etched small enough to be disjointed with each other.
[0061] Taking into account that as the diameter of the colloidal microspheres decreases, the reactive ion etching time, etching power and corrosion time during the wet etching process are correspondingly reduced, in order to better obtain a multi-level pyramid microstructure silicon template, preferably, in step S5, during the reactive ion etching process, the etching power is 50W-200W, and the etching time is 2min-100min; during the wet etching process, the corrosion time is 2min-50min.
[0062] Meanwhile, considering the influence of curing time and curing temperature on the molding effect of the multi-level pyramid microstructure, in the present invention, preferably, in step S6, during the curing process, the curing temperature is 25°C-150°C, and the curing time is 0.25h-24h.
[0063] Specifically, in step S6, the method of placing the flexible conductive mixed liquid on the surface of the multi-level pyramid microstructure silicon template includes spin coating, scraping coating, etc. The present invention preferably adopts the spin coating method to place the flexible conductive mixed liquid on the surface of the multi-level pyramid microstructure silicon template. The spin coating speed is 500rpm-3000rpm, and the spin coating time is 30s-60s. Such an arrangement facilitates the control of the thickness of the flexible conductive film.
[0064] In order to better separate the flexible conductive film from the multi-level pyramid microstructure silicon template, before performing step S6, the surface of the multi-level pyramid microstructure silicon template is subjected to hydrophobic treatment. Preferably, the hydrophobic treatment method can be to use a release agent to treat the surface of the multi-level pyramid microstructure silicon template or to place the multi-level pyramid microstructure silicon template in a sealed trimethylchlorosilane environment for 10min-20min. Such an arrangement can not only better separate the flexible conductive film from the multi-level pyramid microstructure silicon template, but also realize the reuse of the multi-level pyramid microstructure silicon template.
[0065] At the same time, the present invention also provides a flexible conductive film, which is prepared by the above-mentioned method for preparing a flexible conductive film, and the surface of the flexible conductive film has a multi-level pyramid microstructure, such as Figure 2 As shown, the multi-level pyramid microstructure 2 includes a first pyramid 4 and a second pyramid 5 arranged on the side wall of the first pyramid, wherein the height of the first pyramid 4 is 500nm-200μm, and the height of the second pyramid 5 is 100nm-100μm. The flexible conductive film not only has excellent flexibility and conductive properties, but also because the multi-level pyramid microstructure has a large number of levels, the prepared flexible pressure sensor can improve the sensitivity while also improving the detection range and reliability.
[0066] In one embodiment, the center distance between adjacent first pyramids is 1 μm-500 μm.
[0067] In one embodiment, the thickness of the flexible conductive film is 50 μm-500 μm.
[0068] In addition, if Figure 2 As shown, the present invention also provides a flexible pressure sensor, comprising:
[0069] A first substrate 1, wherein the first substrate 1 is the flexible conductive film as described above;
[0070] The second substrate 3 includes a flexible substrate and an electrode (not shown) arranged on a surface of the flexible substrate. The second substrate 3 is stacked on the first substrate 1, and the electrode is in contact with part of the multi-level pyramid microstructure 2 to obtain a flexible pressure sensor.
[0071] In one embodiment, the material of the flexible substrate is at least one selected from polydimethylsiloxane, thermoplastic polyurethane elastomer, polytrimethylene carbonate, and polyethylene terephthalate, and more preferably polydimethylsiloxane, which has relatively excellent biocompatibility and thermal stability.
[0072] In one embodiment, the electrode provided on one surface of the flexible substrate is preferably an interdigitated electrode, which can be prepared by referring to the following method: treating the flexible substrate with oxygen plasma, and then preparing it by surface printing or 3D printing, and curing it at 25°C-150°C to obtain the interdigitated electrode.
[0073] It should be noted that the electrode contacts part of the multi-level pyramid microstructure, that is, in the initial state, the electrode only contacts the surface of the first-level pyramid microstructure with the highest height. As the pressure increases, the contact area between the first-level pyramid microstructure and the electrode increases.
[0074] At the same time, it should be noted that in the present invention, a flexible conductive film is directly used as the first substrate, so that it has both conductive and flexible effects. At the same time, the flexible substrate in the second substrate is also flexible. Therefore, under sufficient pressure, electrical contact can be achieved between the multi-level pyramid microstructure and the electrode.
[0075] In one embodiment, the preparation method of the flexible pressure sensor is as follows:
[0076] A flexible conductive film having a hierarchical pyramid microstructure on its surface is used as a first substrate;
[0077] The flexible substrate is treated with oxygen plasma, and then the interdigital electrodes are 3D printed on the surface. Two thin wires are cut and placed at the two ends of the interdigital electrodes respectively, and then a layer of conductive silver glue is applied to fix the wires to obtain a second substrate.
[0078] The second substrate is stacked on the first substrate so that the electrode contacts part of the multi-level pyramid microstructure, and then the first substrate and the second substrate are packaged with 3M tape to obtain a flexible pressure sensor.
[0079] In this flexible pressure sensor, under the action of pressure, the first-level pyramid microstructure with the highest height is deformed first, so that the contact area between the flexible conductive film and the electrode increases, the conductive path of the flexible pressure sensor increases, the sensitivity curve is a straight line, and the sensitivity is high. As the pressure gradually increases, the second-level pyramid microstructure, the third-level pyramid microstructure, the fourth-level pyramid microstructure, etc., which are the next highest, contact the electrode in turn, further increasing the conductive path of the flexible pressure sensor and maintaining the sensitivity of the flexible pressure sensor. Therefore, the saturated contact area of the flexible pressure sensor can be increased by multi-level pyramid microstructures, the conductive path is increased, and its pressure linear response range is effectively extended, thereby improving the sensitivity of the sensor while also improving the detection range and reliability.
[0080] Hereinafter, the flexible conductive film and the preparation method thereof, and the flexible pressure sensor will be further described through the following specific embodiments.
[0081] It should be noted that the reagents and raw materials involved in the present invention can all be purchased from the market.
[0082] Example 1
[0083] 0.1 g of carbon nanotubes were dispersed in 5 g of tetrahydrofuran solution, ultrasonicated for 30 min, and then magnetically stirred for 1 h. Then, 1 g of polydimethylsiloxane (PDMS) was added and the mixture was stirred and mixed evenly. At the same time, the tetrahydrofuran was heated in a water bath at 70 °C to volatilize. Then, 0.1 g of curing agent was added and stirred evenly at room temperature. Finally, the mixture was placed in a vacuum condition of 0.1 Torr for 30 min to remove bubbles to obtain a flexible conductive mixed solution.
[0084] A stock solution of polystyrene colloidal microspheres with a diameter of 1 μm and a stock solution of polystyrene colloidal microspheres with a diameter of 2 μm were mixed in a volume ratio of 1:1 to obtain a mixed stock solution, and then anhydrous ethanol was added, wherein the volume ratio of the mixed stock solution to the anhydrous ethanol was 1:1.2, and ultrasonication was performed for 10 minutes. After uniform mixing, a mixed solution containing the first colloidal microspheres was obtained.
[0085] The stock solution of polystyrene colloidal microspheres with a diameter of 200 nm and anhydrous ethanol were mixed in a volume ratio of 1:1.2, and ultrasonicated for 10 minutes to obtain a mixed solution containing the second colloidal microspheres.
[0086] Use a pipette to drop the mixed solution containing the first colloidal microspheres obtained above on a hydrophilic and crystal-oriented <100> The silicon wafer is placed on the surface of the silicon wafer, and after the diffusion is uniform, the silicon wafer is slowly placed in water, and two drops of SDS solution with a mass fraction of 2% are added to form a single layer of dense first colloidal microsphere film on the water surface. Then, the first colloidal microsphere film on the water surface is picked up with a clean silicon wafer, placed on a flat heater, and heated at 110°C for 1 minute to evaporate the water and slightly melt the bottom of the first colloidal microsphere to fix it on the silicon wafer. Next, the first colloidal microsphere film on the silicon wafer is etched with oxygen by reactive ion etching (RIE), wherein the gas flux is 100 sccm, the etching power is 100 W, and the etching time is 5 minutes, so that the first colloidal microspheres are etched small, and obvious gaps appear between the first colloidal microspheres, that is, they are separated from each other.
[0087] Afterwards, a 50 nm thick Cr layer was deposited on the silicon wafer with the first colloidal microspheres by magnetron sputtering, and then the first colloidal microspheres were removed by tape to obtain a silicon wafer with Cr holes of different diameters; the silicon wafer with Cr holes of different diameters was placed in a NaOH standard titration solution for wet etching, wherein the corrosion temperature was 80°C and the corrosion time was 5 min, so that the Cr holes were corroded into inverted pyramid cone etch pits to obtain a first pyramid microstructure silicon template, which was then hydrophilic treated to obtain a hydrophilic first pyramid microstructure silicon template.
[0088] Use a pipette to drop the solution containing the second colloidal microspheres onto the hydrophilic and crystalline <100> After the clean silicon wafer is evenly diffused, it is placed in water, and two drops of SDS solution with a mass fraction of 2% are added to form a single layer of dense second colloidal microsphere film on the water surface. Then, the second colloidal microsphere film on the water surface is picked up by the hydrophilic first pyramid microstructure silicon template obtained above, and placed on a flat heater, heated at 110°C for 1 minute, evaporating the water and slightly melting the bottom of the first colloidal microsphere to fix it on the silicon wafer. Next, the second colloidal microsphere film on the first pyramid microstructure silicon template is etched with oxygen by reactive ion etching (RIE), wherein the gas flux is 100 sccm, the etching power is 50 W, and the etching time is 2 minutes, so that the second colloidal microspheres are etched small, and obvious gaps appear between the second colloidal microspheres, that is, they are separated from each other. Afterwards, a 50 nm thick Cr layer was deposited on the first pyramid microstructure silicon template with the second colloidal microspheres by magnetron sputtering, and then the second colloidal microspheres were removed using a tetrahydrofuran solution. Subsequently, the template was placed in a NaOH standard titration solution for wet etching, wherein the corrosion temperature was 80°C and the corrosion time was 2 min to obtain a multi-level pyramid microstructure silicon template. The multi-level pyramid microstructure silicon template was then sealed in a trimethylchlorosilane environment for 15 min to obtain a hydrophobic treated multi-level pyramid microstructure silicon template.
[0089] The flexible conductive mixed liquid obtained above is spin-coated on the surface of the multi-level pyramid microstructure silicon template after the hydrophobic treatment obtained above, wherein the spin coating speed is 3000 rpm, the spin coating time is 30 s, and then it is cured at 80°C for 3 hours, and then the cured flexible conductive film is peeled off from the multi-level pyramid microstructure silicon template to obtain a flexible conductive film with a multi-level pyramid microstructure on the surface.
[0090] The flexible conductive film obtained in this embodiment has a multi-level pyramid microstructure on its surface and a thickness of about 50 μm, wherein the height of the first pyramid microstructure in the multi-level pyramid microstructure is about 500nm-1500nm, the middle distance between adjacent first pyramid microstructures is about 1500nm, and the height of the second pyramid microstructure is about 100nm.
[0091] The flexible conductive film having the hierarchical pyramid microstructure on the surface obtained above is used as the first substrate.
[0092] A flexible substrate is treated with oxygen plasma, wherein the material of the flexible substrate is polyethylene terephthalate, and then interdigital electrodes are 3D printed on its surface, two thin wires are cut and placed at both ends of the interdigital electrodes respectively, and then a layer of conductive silver glue is applied to fix the wires to obtain a second substrate.
[0093] The second substrate is stacked on the first substrate so that the interdigitated electrodes are in contact with part of the multi-level pyramid microstructure, and then the first substrate and the second substrate are packaged with 3M tape to obtain a flexible pressure sensor.
[0094] Example 2
[0095] 0.1 g of carbon nanotubes were dispersed in 5 g of tetrahydrofuran solution, ultrasonicated for 30 min, and then magnetically stirred for 1 h. Then, 1 g of polydimethylsiloxane (PDMS) was added and the mixture was stirred and mixed evenly. At the same time, the tetrahydrofuran was heated in a water bath at 70 °C to volatilize. Then, 0.1 g of curing agent was added and stirred evenly at room temperature. Finally, the mixture was placed in a vacuum condition of 0.1 Torr for 30 min to remove bubbles to obtain a flexible conductive mixed solution.
[0096] A stock solution of polystyrene colloidal microspheres with a diameter of 20 μm, a stock solution of polystyrene colloidal microspheres with a diameter of 30 μm, and a stock solution of polystyrene colloidal microspheres with a diameter of 40 μm are mixed in a volume ratio of 1:2:4 to obtain a mixed stock solution, and then anhydrous ethanol is added, wherein the volume ratio of the mixed stock solution to the anhydrous ethanol is 1:1.2, and ultrasonication is performed for 10 minutes. After uniform mixing, a mixed solution containing the first colloidal microspheres is obtained.
[0097] The stock solution of polystyrene colloidal microspheres with a diameter of 2 μm and anhydrous ethanol were mixed in a volume ratio of 1:1.2, and ultrasonicated for 10 minutes to obtain a mixed solution containing the second colloidal microspheres.
[0098] Use a pipette to drop the mixed solution containing the first colloidal microspheres obtained above on a hydrophilic and crystal-oriented <100> The silicon wafer is placed on the surface of the silicon wafer, and after the diffusion is uniform, the silicon wafer is slowly placed in water, and two drops of SDS solution with a mass fraction of 2% are added to form a single layer of dense first colloidal microsphere film on the water surface. Then, the first colloidal microsphere film on the water surface is picked up with a clean silicon wafer, placed on a flat heater, and heated at 110°C for 1 minute to evaporate the water and slightly melt the bottom of the first colloidal microsphere to fix it on the silicon wafer. Next, the first colloidal microsphere film on the silicon wafer is etched with oxygen by reactive ion etching (RIE), wherein the gas flux is 100 sccm, the etching power is 100 W, and the etching time is 60 minutes, so that the first colloidal microspheres are etched small, and obvious gaps appear between the first colloidal microspheres, that is, they are separated from each other. Afterwards, a 50 nm thick Cr layer was deposited on the silicon wafer with the first colloidal microspheres by magnetron sputtering, and then the first colloidal microspheres were removed by tape to obtain a silicon wafer with Cr holes of different diameters; the silicon wafer with Cr holes of different diameters was placed in a NaOH standard titration solution for wet etching, wherein the corrosion temperature was 80°C and the corrosion time was 60 min, so that the Cr holes were corroded into inverted pyramid cone etch pits to obtain a first pyramid microstructure silicon template, which was then hydrophilic treated to obtain a hydrophilic first pyramid microstructure silicon template.
[0099] Use a pipette to drop the solution containing the second colloidal microspheres onto the hydrophilic and crystalline <100> After the clean silicon wafer is evenly diffused, it is placed in water, and two drops of SDS solution with a mass fraction of 2% are added to form a single layer of dense second colloidal microsphere film on the water surface. Then, the second colloidal microsphere film on the water surface is picked up by the hydrophilic first pyramid microstructure silicon template obtained above, and placed on a flat heater, heated at 110° C. for 1 minute, the water is evaporated and the bottom of the first colloidal microsphere is slightly melted, so that it is fixed on the silicon wafer. Next, the second colloidal microsphere film on the first pyramid microstructure silicon template is etched by oxygen using reactive ion etching (RIE), wherein the gas flux is 100 sccm, the etching power is 50 W, and the etching time is 5 minutes, so that the second colloidal microspheres are etched small, and obvious gaps appear between the second colloidal microspheres, that is, they are separated from each other. Afterwards, a 50 nm thick Cr layer was deposited on the first pyramid microstructure silicon template with the second colloidal microspheres by magnetron sputtering, and then the second colloidal microspheres were removed by using a tetrahydrofuran solution, followed by wet etching in a NaOH standard titration solution, wherein the corrosion temperature was 80°C and the corrosion time was 8 min to obtain a multi-level pyramid microstructure silicon template, and then the multi-level pyramid microstructure silicon template was sealed in a trimethylchlorosilane environment for 15 min to obtain a hydrophobic treated multi-level pyramid microstructure silicon template.
[0100] The flexible conductive mixed liquid obtained above is spin-coated on the surface of the multi-level pyramid microstructure silicon template after the hydrophobic treatment obtained above, wherein the spin coating speed is 1000 rpm, the spin coating time is 30 s, and then it is cured at 80°C for 3 hours, and then the cured flexible conductive film is peeled off from the multi-level pyramid microstructure silicon template to obtain a flexible conductive film with a multi-level pyramid microstructure on the surface.
[0101] The flexible conductive film obtained in this embodiment has a multi-level pyramid microstructure on its surface and a thickness of about 200 μm, wherein the height of the first pyramid microstructure in the multi-level pyramid microstructure is about 5 μm-20 μm, the middle distance between adjacent first pyramid microstructures is about 30 μm, and the height of the second pyramid microstructure is about 1 μm.
[0102] In this embodiment, a flexible pressure sensor is prepared according to the method in embodiment 1.
[0103] Example 3
[0104] Compared with Example 2, the only difference is that in Example 3, the stock solution of polystyrene colloidal microspheres with a diameter of 20 μm, the stock solution of polystyrene colloidal microspheres with a diameter of 30 μm, and the stock solution of polystyrene colloidal microspheres with a diameter of 40 μm are mixed in a volume ratio of 1:1:1 to obtain a mixed stock solution, and then anhydrous ethanol is added, the volume ratio of the mixed stock solution to the anhydrous ethanol is 1:1.3, and ultrasonication is performed for 10 minutes. After uniform mixing, a mixed solution containing the first colloidal microspheres is obtained, and the other conditions are the same.
[0105] The flexible conductive film obtained in this embodiment has a multi-level pyramid microstructure on the surface, with a thickness of about 200μm, a height of the first pyramid microstructure in the multi-level pyramid microstructure of about 5μm-20μm, an intermediate distance between adjacent first pyramid microstructures of about 30μm, and a height of the second pyramid microstructure of about 1μm.
[0106] In this embodiment, a flexible pressure sensor is prepared according to the method in embodiment 1.
[0107] Example 4
[0108] Compared with Example 1, the only difference is that in Example 4, the stock solution of polystyrene colloidal microspheres with a diameter of 300 nm and anhydrous ethanol are mixed in a volume ratio of 1:1.2, and ultrasonicated for 10 minutes to obtain a mixed solution containing second colloidal microspheres.
[0109] At the same time, the second colloidal microsphere film on the first pyramid microstructure silicon template is etched by oxygen using reactive ion etching (RIE), wherein the gas flux is 100 sccm, the etching power is 50 W, and the etching time is 3 min, so that the second colloidal microspheres are etched small, and obvious gaps appear between the second colloidal microspheres, that is, they are separated from each other. Afterwards, a 50 nm thick Cr layer is deposited on the first pyramid microstructure silicon template with the second colloidal microspheres by magnetron sputtering, and then the second colloidal microspheres are removed by tetrahydrofuran solution, and then placed in a NaOH standard titration solution for wet etching, wherein the etching temperature is 80°C, and the etching time is 3 min, to obtain a multi-level pyramid microstructure silicon template, and then the multi-level pyramid microstructure silicon template is sealed in a trimethylchlorosilane environment for 15 min to obtain a hydrophobic multi-level pyramid microstructure silicon template, and the other conditions are the same.
[0110] The flexible conductive film obtained in this embodiment has a multi-level pyramid microstructure on its surface and a thickness of about 50 μm, wherein the height of the first pyramid microstructure in the multi-level pyramid microstructure is about 500nm-1500nm, the middle distance between adjacent first pyramid microstructures is about 1500nm, and the height of the second pyramid microstructure is about 150nm.
[0111] In this embodiment, a flexible pressure sensor is prepared according to the method in embodiment 1.
[0112] Example 5
[0113] Compared with Example 1, the only difference is that the stock solution of polymethyl acrylate colloidal microspheres is used to replace the stock solution of polystyrene colloidal microspheres, and the other conditions are the same.
[0114] The flexible conductive film obtained in this embodiment has a multi-level pyramid microstructure on its surface and a thickness of about 50 μm, wherein the height of the first pyramid microstructure in the multi-level pyramid microstructure is about 500nm-1500nm, the middle distance between adjacent first pyramid microstructures is about 1500nm, and the height of the second pyramid microstructure is about 100nm.
[0115] In this embodiment, a flexible pressure sensor is prepared according to the method in embodiment 1.
[0116] Comparative Example 1
[0117] 0.1 g of carbon nanotubes were dispersed in 5 g of tetrahydrofuran solution, ultrasonicated for 30 min, and then magnetically stirred for 1 h. Then, 1 g of polydimethylsiloxane (PDMS) was added and the mixture was stirred and mixed evenly. At the same time, the tetrahydrofuran was heated in a water bath at 70 °C to volatilize. Then, 0.1 g of curing agent was added and stirred evenly at room temperature. Finally, the mixture was placed in a vacuum condition of 0.1 Torr for 30 min to remove bubbles to obtain a flexible conductive mixed solution.
[0118] A stock solution of polystyrene colloidal microspheres with a diameter of 20 μm, a stock solution of polystyrene colloidal microspheres with a diameter of 30 μm, and a stock solution of polystyrene colloidal microspheres with a diameter of 40 μm are mixed in a volume ratio of 1:2:4 to obtain a mixed stock solution, and then anhydrous ethanol is added, wherein the volume ratio of the mixed stock solution to anhydrous ethanol is 1:1.2, and ultrasonication is performed for 10 minutes. After uniform mixing, a mixed solution containing the first colloidal microspheres is obtained.
[0119] Use a pipette to drop the mixed solution containing the first colloidal microspheres obtained above on a hydrophilic and crystal-oriented <100> The silicon wafer is placed on the surface of the silicon wafer, and after the diffusion is uniform, the silicon wafer is slowly placed in water, and two drops of SDS solution with a mass fraction of 2% are added to form a single layer of dense first colloidal microsphere film on the water surface. Then, the first colloidal microsphere film on the water surface is picked up with a clean silicon wafer, placed on a flat heater, and heated at 110°C for 1 minute to evaporate the water and slightly melt the bottom of the first colloidal microsphere to fix it on the silicon wafer. Next, the first colloidal microsphere film on the silicon wafer is etched with oxygen by reactive ion etching (RIE), wherein the gas flux is 100 sccm, the etching power is 100 W, and the etching time is 60 minutes, so that the first colloidal microspheres are etched small, and obvious gaps appear between the first colloidal microspheres, that is, they are separated from each other. Afterwards, a 50 nm thick Cr layer was deposited on the silicon wafer with the first colloidal microspheres by magnetron sputtering, and then the first colloidal microspheres were removed by tape to obtain a silicon wafer with Cr holes of different diameters; the silicon wafer with Cr holes of different diameters was placed in a NaOH standard titration solution for wet etching, wherein the corrosion temperature was 80°C and the corrosion time was 60 min, so that the Cr holes were corroded into inverted pyramid cone etch pits to obtain a first pyramid microstructure silicon template, and then the first pyramid microstructure silicon template was sealed in a trimethylchlorosilane environment for 15 min to obtain the first pyramid microstructure silicon template after hydrophobic treatment.
[0120] The flexible conductive mixed liquid obtained above is spin-coated on the surface of the first pyramid microstructure silicon template after the hydrophobic treatment obtained above, wherein the spin coating speed is 1000 rpm, the spin coating time is 30 s, and then cured at 80°C for 3 hours, and then the cured flexible conductive film is peeled off from the first pyramid microstructure silicon template to obtain a flexible conductive film with a multi-level pyramid microstructure on the surface.
[0121] The comparative example obtained a flexible conductive film having a multi-level pyramid microstructure on the surface, the thickness of the flexible conductive film was about 200 μm, the height of the first pyramid microstructure in the multi-level pyramid microstructure was about 5 μm-20 μm, and the middle distance between adjacent first pyramid microstructures was about 30 μm.
[0122] In this comparative example, a flexible pressure sensor was prepared according to the method in Example 1.
[0123] Comparative Example 2
[0124] 0.1 g of carbon nanotubes were dispersed in 5 g of tetrahydrofuran solution, ultrasonicated for 30 min, and then magnetically stirred for 1 h. Then, 1 g of polydimethylsiloxane (PDMS) was added and the mixture was stirred and mixed evenly. At the same time, the tetrahydrofuran was heated in a water bath at 70 °C to volatilize. Then, 0.1 g of curing agent was added and stirred evenly at room temperature. Finally, the mixture was placed in a vacuum condition of 0.1 Torr for 30 min to remove bubbles to obtain a flexible conductive mixed solution.
[0125] The stock solution of polystyrene colloidal microspheres with a diameter of 2 μm and anhydrous ethanol were mixed in a volume ratio of 1:1.2, and ultrasonicated for 10 minutes to obtain a mixed solution containing the second colloidal microspheres.
[0126] Use a pipette to drop the mixed solution containing the second colloidal microspheres obtained above on a hydrophilic and crystal-oriented <100> After the diffusion is uniform, the silicon wafer is slowly placed in water, and two drops of SDS solution with a mass fraction of 2% are added to form a single layer of dense second colloidal microsphere film on the water surface. Then, the first colloidal microsphere film on the water surface is picked up with a clean silicon wafer, placed on a flat heater, and heated at 60°C for 1 minute to completely evaporate the water. Next, the second colloidal microsphere film on the first pyramid microstructure silicon template is etched with oxygen by reactive ion etching (RIE), wherein the gas flux is 100 sccm, the etching power is 50 W, and the etching time is 5 minutes, so that the second colloidal microspheres are etched small, and obvious gaps appear between the second colloidal microspheres, that is, they are separated from each other. Afterwards, a 50 nm thick Cr layer was deposited on the first pyramid microstructure silicon template with the second colloidal microspheres by magnetron sputtering, and then the second colloidal microspheres were removed by using a tetrahydrofuran solution, followed by wet etching in a NaOH standard titration solution, wherein the corrosion temperature was 80°C and the corrosion time was 8 min to obtain a pyramid microstructure silicon template, and then the pyramid microstructure silicon template was sealed in a trimethylchlorosilane environment for 15 min to obtain a hydrophobic treated pyramid microstructure silicon template.
[0127] The flexible conductive mixed liquid obtained above is spin-coated on the surface of the hydrophobic treated pyramid microstructure silicon template obtained above, wherein the spin coating speed is 1000 rpm and the spin coating time is 30 s, and then cured at 80°C for 3 hours, and then the cured flexible conductive film is peeled off from the pyramid microstructure silicon template to obtain a flexible conductive film with a pyramid microstructure on the surface.
[0128] The flexible conductive film with a pyramid microstructure on the surface obtained in this embodiment has a thickness of about 200 μm, wherein the height of the pyramid microstructure is about 1 μm, and the intermediate distance between adjacent pyramid microstructures is 2 μm.
[0129] In this comparative example, a flexible pressure sensor was prepared according to the method in Example 1.
[0130] Comparative Example 3
[0131] Compared with Example 2, the only difference is that the stock solution of polystyrene colloidal microspheres with a diameter of 20 μm, the stock solution of polystyrene colloidal microspheres with a diameter of 30 μm, and the stock solution of polystyrene colloidal microspheres with a diameter of 100 μm are mixed in a volume ratio of 1:2:8 to obtain a mixed stock solution, and then anhydrous ethanol is added, wherein the volume ratio of the mixed stock solution to anhydrous ethanol is 1:1.2, and ultrasonication is performed for 10 minutes. After uniform mixing, a mixed solution containing the first colloidal microspheres is obtained.
[0132] In this comparative example, a flexible pressure sensor was prepared according to the method in Example 1.
[0133] Comparative Example 4
[0134] Compared with Example 2, the only difference is that the stock solution of polystyrene colloidal microspheres with a diameter of 500 nm and anhydrous ethanol are mixed in a volume ratio of 1:1.2, and ultrasonicated for 10 minutes to obtain a mixed solution containing the second colloidal microspheres.
[0135] In this comparative example, a flexible pressure sensor was prepared according to the method in Example 1.
[0136] Comparative Example 5
[0137] Compared with Example 2, the only difference is that the stock solution of polystyrene colloidal microspheres with a diameter of 10 μm and anhydrous ethanol are mixed in a volume ratio of 1:1.2, and ultrasonicated for 10 minutes to obtain a mixed solution containing the second colloidal microspheres.
[0138] In this comparative example, a flexible pressure sensor was prepared according to the method in Example 1.
[0139] Comparative Example 6
[0140] Compared with Example 2, the only difference is that the stock solution of polystyrene colloidal microspheres with a diameter of 20 μm, the stock solution of polystyrene colloidal microspheres with a diameter of 30 μm, and the stock solution of polystyrene colloidal microspheres with a diameter of 40 μm are mixed in a volume ratio of 1:4:10 to obtain a mixed stock solution, and then anhydrous ethanol is added, wherein the volume ratio of the mixed stock solution to anhydrous ethanol is 1:1.2, and ultrasonication is performed for 10 minutes. After uniform mixing, a mixed solution containing the first colloidal microspheres is obtained.
[0141] In this comparative example, a flexible pressure sensor was prepared according to the method in Example 1.
[0142] The relationship between the current change rate and pressure of the flexible pressure sensors of Example 2 of the present invention and Comparative Examples 1-6 was tested. The results are as follows: Figure 3The linear detection range of the sensor of Example 2 of the present invention is 0-1000 kPa, and the sensitivity is about 555 kPa -1 , the linearity of the fitting is 0.993, that is, the detection sensitivity and linearity of the flexible pressure sensor of the present invention are both high at lower and higher pressures. The linear detection range of the sensor in comparative example 1 is 0-440 kPa, and the sensitivity in 0-1000 kPa is about 189 kPa. -1 , the linear goodness of fit is 0.939; the linear detection range of the sensor in comparative example 2 is 0-160kPa, and the sensitivity within 0-1000kPa is about 22kPa -1 , the linear goodness of fit is 0.912; the linear detection range of the sensor in comparative example 3 is 0-280kPa, and the sensitivity within 0-1000kPa is about 95kPa -1 , the linear goodness of fit is 0.922; the linear detection range of the sensor of comparative example 4 is 0-400kPa, and the sensitivity within 0-1000kPa is about 386kPa -1 , the linear goodness of fit is 0.918; while the linear detection range of the sensor in comparative example 5 is 0-640kPa, and the sensitivity within 0-1000kPa is about 242kPa -1 , the linear goodness of fit is 0.862; while the linear detection range of the sensor in comparative example 6 is 0-1000kPa, and the sensitivity within 0-1000kPa is about 483kPa -1 , the linear goodness of fit is 0.986. It can be seen that the sensitivity and linear detection range of comparative examples 1-6 are significantly weaker than those of the flexible pressure sensor of the present invention.
[0143] Specifically, the microstructure of the flexible pressure sensor of Comparative Example 1 only has the first pyramid microstructure, resulting in insufficient microstructure richness and less deformable part than Example 2 of the present invention. Therefore, the linear detection range, sensitivity, and linear fitting goodness are all smaller than Example 2. Since the flexible pressure sensor of Comparative Example 2 only has the second pyramid microstructure, and the pyramid cones have the same height without a hierarchical structure and are smaller in size than Comparative Example 1, the linear detection range, sensitivity, and linear fitting goodness are all smaller than Comparative Example 1.
[0144] Since the diameter ratio A of the first colloidal microspheres in comparative example 3 exceeds the limited range of 1:1<A≤4:1, the 20μm colloidal microspheres agglomerate on the surface of the 100μm colloidal microspheres due to tension during self-assembly, and the other 20μm microspheres and 30μm microspheres that have not agglomerated are not evenly distributed, so the first pyramid cone structure is deformed into irregular protrusions and irregular distribution of 30μm high pyramid cones. The linear detection range, sensitivity and fitting linearity are slightly higher than those of comparative example 2 but lower than those of comparative example 1.
[0145] Since the first pyramid cone of comparative example 4 is complete, but the height of the second pyramid cone is too small, the sensitivity is improved to a certain extent, but the saturation of the current cannot be effectively compensated, so the linear detection range is lower than the linear detection range of the flexible pressure sensor of Example 2 of the present invention, but is the same as that of comparative example 1. The sensitivity in the low pressure range is higher than that of Example 2, and the linear fitting goodness is lower than that of Example 2.
[0146] Since the first pyramid cone of Comparative Example 5 is complete, but the height of the second pyramid cone is too large and the number is small, the linear detection range is higher than that of Comparative Example 4 and Comparative Example 1, but the sensitivity in the low pressure range is higher than that of Comparative Example 1 and lower than that of Comparative Example 4.
[0147] Since the original solution ratio of the first colloidal microspheres in Comparative Example 6 exceeds the specified range, the first pyramid cones are unevenly distributed and the pyramid cones of the same height are locally agglomerated. Therefore, the linear detection range is the same as that of Example 2, and the sensitivity and the linear fitting goodness are slightly lower than those of Example 2.
[0148] It can be seen that the present invention, through the synergistic effect of the first pyramid and the second pyramid, enables the prepared flexible pressure sensor to improve sensitivity while also improving detection range and reliability, and has high linearity. At the same time, if the diameter of the first colloidal microsphere, the diameter ratio of any two different diameters of the first colloidal microspheres, or the diameter ratio of the second colloidal microsphere to the first colloidal microsphere does not meet the range required by the present invention, it will have a significant impact on the sensitivity and detection range of the flexible pressure sensor.
[0149] In addition, the flexible pressure sensor prepared by the present invention can be used as a wearable electronic product, and has great application prospects in intelligent robots and human physiological signal monitoring. For example, in human physiological signal monitoring, the flexible pressure sensor can be attached to the surface of the human chest to monitor the heart rate, attached to the wrist to detect arterial pulsation, and attached to the throat to detect vocal cord vibration, etc.
[0150] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0151] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a flexible conductive film, characterized in that: The following steps are involved: Provide hydrophilic and crystalline <100> A silicon substrate, a flexible conductive mixed liquid, a mixed liquid containing at least two first colloidal microspheres of different diameters, and a mixed liquid containing second colloidal microspheres of a single diameter; A mixed solution containing at least two first colloidal microspheres of different diameters is placed in a hydrophilic and crystallographically oriented <100> The silicon substrate is self-assembled to form a single-layer first colloidal microsphere film, wherein the diameter of the first colloidal microsphere is 1 μm-500 μm, and the diameter ratio of any two first colloidal microspheres with different diameters is A, 1:1<A≤4:1; Performing reactive ion etching on the first colloidal microsphere film, and then performing magnetron sputtering deposition to form a first metal layer, removing the first colloidal microspheres, and then performing wet etching to obtain a first pyramid microstructure silicon template; The first pyramid microstructure silicon template is subjected to hydrophilic treatment, and then the mixed solution containing second colloidal microspheres of a single diameter is self-assembled on the surface of the first pyramid microstructure silicon template to form a single-layer second colloidal microsphere film, wherein the diameter of the second colloidal microspheres is 5%-20% of the diameter of the first colloidal microspheres; Performing reactive ion etching on the second colloidal microsphere film, and then performing magnetron sputtering to form a second metal layer, removing the second colloidal microspheres, and then performing wet etching to obtain a multi-level pyramid microstructure silicon template; and The flexible conductive mixed liquid is placed on the surface of the multi-level pyramid microstructure silicon template, and after curing and peeling, a flexible conductive film with a multi-level pyramid microstructure on the surface is obtained.
2. The method for preparing a flexible conductive film according to claim 1, characterized in that: The mixed solution containing at least two first colloidal microspheres of different diameters is obtained by mixing at least two stock solutions of first colloidal microspheres of different diameters and anhydrous ethanol, wherein the volume ratio of the stock solutions of any two first colloidal microspheres of different diameters is M, 1:1≤M≤8:1, and M represents the volume ratio of the stock solution of the first colloidal microspheres with a larger diameter to the stock solution of the first colloidal microspheres with a smaller diameter.
3. The method for preparing the flexible conductive film according to claim 1, characterized in that: Before placing the flexible conductive mixed liquid on the surface of the multi-level pyramid microstructure silicon template, the surface of the multi-level pyramid microstructure silicon template is subjected to a hydrophobic treatment.
4. The method for preparing a flexible conductive film according to claim 1, characterized in that: The self-assembly adopts gas-liquid-interface self-assembly; And / or, the first colloidal microspheres and the second colloidal microspheres are both selected from at least one of polystyrene colloidal microspheres, polymethyl acrylate colloidal microspheres, polyacrylamide colloidal microspheres, and polybutyl acrylate colloidal microspheres.
5. The method for preparing a flexible conductive film according to claim 1, characterized in that: In the reactive ion etching process, oxygen is used as the etching gas, the etching power is 50W-400W, and the etching time is 2min-120min; and / or, during the wet etching process, the etching temperature is 80° C.-90° C., and the etching time is 2 min-60 min; And / or, during the curing process, the curing temperature is 25° C.-150° C., and the curing time is 0.25 h-24 h.
6. The method for preparing a flexible conductive film according to claim 1, characterized in that: The thickness of the first metal layer and the second metal layer are both 50nm-100nm.
7. The method for preparing a flexible conductive film according to claim 1, characterized in that: The flexible conductive mixed liquid is formed by mixing polymer monomers, conductive materials and curing agents, wherein the mass fraction of the conductive materials in the flexible conductive mixed liquid is 5%-15%.
8. The method for preparing a flexible conductive film according to claim 7, characterized in that: The material of the polymer monomer is selected from at least one of polydimethylsiloxane, polyurethane elastomer, and polytrimethylene carbonate; And / or, the conductive material is selected from at least one of carbon nanotubes, graphene, and silver nanowires.
9. A flexible conductive film, characterized in that: The flexible conductive film is prepared by the method for preparing a flexible conductive film according to any one of claims 1 to 8, and the multi-level pyramid microstructure includes a first pyramid and a second pyramid arranged on a side wall of the first pyramid, wherein the height of the first pyramid is 500nm-200μm, and the height of the second pyramid is 100nm-100μm.
10. A flexible pressure sensor, characterized in that: include: A first substrate, wherein the first substrate is the flexible conductive film as claimed in claim 9; The second substrate includes a flexible substrate and an electrode disposed on a surface of the flexible substrate. The second substrate is stacked on the first substrate, and the electrode contacts a portion of the multi-level pyramid microstructure to obtain a flexible pressure sensor.
Citation Information
Cited By
Preparation method and application of surface pyramid multistage ordered piezoresistive sensor
CN120101984A
Preparation method and application of a surface pyramid multi-level ordered piezoresistive sensor
CN120101984B
